Pengaruh Pengembangan Diri (People Devlopment), Pelatihan Dan Penghargaan (Reward) Terhadap Motivasi yang Berdampak Pada kinerja karyawan Di Lingkungan kecamatan Tayu Pati - Badriyati, Laila Nurul; Sijabat, Rauly; Prabowo, Heri (Jurnal Ilmiah Manajemen Bisnis dan Ekonomi Kreatif, 2025)
This study aims to analyze the influence of self-development, training and rewards on motivation which has an impact on employee performance in Tayu, Pati District. The data analysis method in this study uses Structural Equation Modeling (SEM) which was run on Smart PLS. Data was collected by observations and questionnaire which was distributed to 84 people. The results show that self-development does not have a positive and significant effect on employee performance, self-development does not have a positive and significant effect on motivation, self-development through motivation has no direct, significant effect on performance, training on performance has no significant effect, training on motivation has no positive effect, training has no positive effect on motivation on performance, awards for performance have no positive effect, rewards for motivation have a positive and significant effect, rewards for motivation have an indirect positive effect, motivation has a positive and significant effect.